2007
DOI: 10.1300/j184v11n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment-Guided Neurofeedback for Autistic Spectrum Disorder

Abstract: There is a need for effective interventions to address the core symptoms and problems associated with autistic spectrum disorder (ASD). Behavior therapy improves communication and behavioral functioning. Additional treatment options include psychopharmacological and biomedical interventions. Although these approaches help children with autistic problems, they may be associated with side effects, risks or require ongoing or long-term treatment. Neurofeedback is a noninvasive approach shown to enhance neuroregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 66 publications
11
96
0
3
Order By: Relevance
“…These changes were evident across frontal, temporal, and limbic regions. The results of the current study also support and expand upon the findings found previously (Coben & Padolsky, 2007). In our earlier study, we achieved an 89% success rate that was coupled with a 40% reduction in core ASD symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These changes were evident across frontal, temporal, and limbic regions. The results of the current study also support and expand upon the findings found previously (Coben & Padolsky, 2007). In our earlier study, we achieved an 89% success rate that was coupled with a 40% reduction in core ASD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study (Coben & Padolsky, 2007), we presented evidence supporting the efficacy of connectivity-guided EEG biofeedback for ASD. Parental judgment of clinical improvement was positive in 89% (33 of 37 subjects) of the experimental group.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The reliability and validity of quantitative EEG (qEEG) have been sufficiently assessed and confirmed (Thatcher, 2010). We have previously shown qEEG data to be useful in impacting outcome of NF intervention for children on the autistic spectrum (Coben & Myers, 2010;Coben & Padolsky, 2007). All EEG data was subjected to manual artifacting procedures conducted by a professional with more than 30 years' experience.…”
Section: Methods Participant Characteristicsmentioning
confidence: 99%
“…This EEG signal is processed and compared to database of normal subjects in order to reveal a profile of abnormalities (Coben & Padolsky, 2007). Changes in EEG patterns as a result of NFB have been associated with regulation of cerebral blood flow, metabolism, and neurotransmitter function (Lubar, 1997).…”
Section: Introductionmentioning
confidence: 99%